Chapter Trusted Smart Statistics: new statistics for decision makers. The Istat's experience - De Cubellis, Massimo (Proceedings e report, 2023)
The Trusted Smart statistics is an expression introduced by Eurostat to indicate the mature phase of the production of statistics based on Big Data and the transition from statistics based on traditional data sources to statistics created with new data sources. In this paper we will discuss: the impact of digital transformation in National Statistical Institutes (NSIs) and in their production of official statistics, how NSIs have adapted new research paradigms, how digital transformation has prompted National Statistical Institutes to adapt their production processes by exploiting new data sources, with the aim of improving statistical information also in terms of eg. of timeliness and granularity and strengthening their role in the ecosystem of scientific knowledge. This transformation process involves the entire organization in order to guarantee the same levels of relevance, quality and trust as traditional statistics. Istat, thanks to new data sources, increasingly performing technologies and specific skills, has positively seized the opportunities offered by the general context and has recently established a Trusted Smart Statistics Center (TSS Center) to have a governing body that systematically guides organizational adaptation at a technological, methodological, ethical, legal, communication and human resource level. The objective of the TSS Center is to capitalize the investments that Istat has made in European (e.g. ESSNet) and international (e.g. UNECE HLG-MOS) research projects, transferring the lessons learned and the know-how acquired in the statistics of new processes productive. At an organizational level, the TSS Center has the task of designing a sustainable organizational structure that helps and supports the individual company components to work in a systemic, coherent and synergistic way to create the new Trusted Smart Statistics production system.